USULAN PERBAIKAN KUALITAS MASTER BATCH WHITE MENGGUNAKAN METODE FAULT TREE ANALYSIS (FTA) DAN FAILURE MODE EFFECT ANALYSIS (FMEA) DENGAN PENDEKATAN DESIGN OF EXPERIMENT (DOE) DI PT.XYZ - Putra, Angga Trisna (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
PT XYZ, located in ABC industrial area, Serang Regency, Banten, is a Masterbatch manufacturer in Indonesia that faces challenges in maintaining the quality of Masterbatch White, particularly related to color mismatch. This study aims to identify the largest defects, causal factors, and proposed improvements to reduce product defects using Fault Tree Analysis (FTA) and Failure Mode And Effect Analysis (FMEA) and action plants with Design of experiment (Doe).  Through the analysis of Fault Tree Analysis (FTA), Pareto Diagram, and Failure Mode And Effect Analysis (FMEA) and action plant with Design of experiment (Doe), this study found two main factors causing defects. First, non-standard color with an RPN value of 638, which resulted from inappropriate material formulation. Improvement recommendations included material formulation adjustments for two suppliers: from China, with a composition of 70% pigment, 23% resin, and 7% additives and from Europe, with a composition of 70% pigment, 22% resin, and 8% additives. Second, the defect of inappropriate piece size with an RPN value of 378 is caused by blunt knives. To overcome this, it is recommended to change knives every 8 hours and preventive measures to maintain the condition of knives during the production process. These proposed improvements are expected to reduce product defects and improve the quality of Masterbatch White